Perlindungan Hukum HAKI Dalam Perjanjian Waralaba - Bonaraja Purba; Hasyim Hasyim; Aulia Nurfitriana; Sarma Juliana Silaban; Sophia Hanum; Tinti Sriyani (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
Franchise growth in Indonesia shows an increase with the growth and development of the franchise local. The essence of the franchise concept that has a selling point lies in the rights Intellectual Property of a franchise, as a special right owned by individuals or business entities against business systems with business characteristics in order to market goods and/or services that have been proven successful and can be exploited and/or used by other parties. For that protection of Intellectual Property Rights in the agreement franchise, is very important. The franchise business concept has become one of the centers of attention which gave a new breakthrough in the dynamics of the Indonesian economy, especially as a form of business development, considering Franchising is a business that has proven its success. So much effort which was then franchised. This research is a research that uses library research, so the data is required in the form of bibliographical data in the form of legal material.